PENGEMBANGAN BUKU CERITA RAKYAT SUMATERA SELATAN PADA PEBELAJARAN PPKN KELAS III SEKOLAH DASAR - Desti Seri Hanggrraini; Bukman Lian; Kiki Aryaningrum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
To increase student learning motivation, teachers play an important role in creating an interesting learning atmosphere, one of which is through learning media. One of the effective media is the South Sumatra folklore book, a form of literature, which helps increase motivation in learning PPkn. This study aims to develop learning media for grade III in elementary schools that are valid, practical and potential effects. The type of research used is reseach and development (R&D) with the ADDIE development model. Data collection techniques through tests, questionnaires and documentation. With a population of 23 grade II students of SDN 16 Palembang. Data analysis techniques used through quantitative techniques and qualitative techniques. The results showed that the validation results obtained an assessment with a percentage of 90%